DISRUPTION OR TRANSFORMATION? THE IMPACT OF ARTIFICIAL INTELLIGENCE ON PEDAGOGIC COMPETENCE, ACADEMIC INTEGRITY, AND THE FUTURE OF HIGHER EDUCATION IN INDONESIA - Hairuddin Cikka; Mokh. Ulil Hidayat; M. Jen Ismail (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study aims to analyze the impact of artificial intelligence (AI) on pedagogical competence, academic integrity, and the future of higher education in Indonesia, from the perspectives of disruption and transformation. This study uses a qualitative approach, employing the library research method, by analyzing reputable scientific literature published over the last five years. The results of the study show that AI plays a strategic role in enhancing the effectiveness and personalization of learning, but it also poses serious challenges related to lecturers' pedagogical competencies and the potential for violations of academic integrity. AI integration has encouraged a shift in lecturers' roles to become facilitators of technology-based learning, but this shift has not been fully supported by adequate digital literacy and institutional readiness, especially in Indonesian higher education. On the other hand, the emergence of generative AI magnifies the risks of plagiarism and technological dependence, requiring a comprehensive ethical and regulatory approach. The findings of this study confirm that AI has a dual character as a disruptive and transformative technology, with its impact highly dependent on the implementation strategy. Therefore, integrative efforts are needed that include strengthening pedagogic competence, developing adaptive policies, and instilling the value of academic integrity to ensure optimal and sustainable use of AI in higher education. This research is expected to make theoretical and practical contributions to the development of a higher education system responsive to technological developments in the digital era.